Assessment of cellulose nanofibers from bolaina blanca wood obtained at three shaft heights - Arango-Perez, Sergio Andre; Gonzales-Mora, Héctor Enrique; Ponce-Alvarez, Silvia Patricia; Gutarra-Espinoza, Abel Aurelio; Cárdenas-Oscanoa, Aldo Joao (Maderas. Ciencia y Tecnología, 2023)
This study evaluated cellulose nanofibers from bolaina blanca wood (Guazuma crinita) obtained at different heights of the longitudinal axis of the shaft of trees from a three-and-a-half-year-old plantation. The wood was subjected to pulping, bleaching and subsequent mechanical milling using a Changsha Samy XYQM-2L planetary ball mill to obtain cellulose nanofibers. The product was characterised using analytical techniques: scanning electron microscopy, X-ray diffraction, thermogravimetric analysis, Fourier transform infrared spectroscopy, ultraviolet–visible spectroscopy. Additionally, the degree of polymerisation was determined. The effect of longitudinal position on cellulose nanofibers characteristics was evaluated by comparing means using ANOVA and Kruskal–Wallis statistical tests. The yield of cellulose nanofibers production from the high, middle and basal sections was 32,1 %, 33,6 % and 31 %, respectively. The obtained cellulose nanofibers exhibited a significantly larger diameter for the high zone (84 nm) compared with the middle (75 nm) and basal (69 nm) zones; the length remained above the micrometre range. With respect to degree of polymerisation, a decrease was evidenced with respect to the increase in shaft height; the basal zone exhibited a degree of polymerisation of 300, a significantly higher value than the middle and high zones, which exhibited degree of polymerisation of 249 and 211, respectively. The product showed typical cellulose type I polymorphism and crystallinity indexes of 76 %, 93 % and 96 % for the high, middle and basal sections, respectively. Regarding the thermostability of cellulose nanofibers, the maximum degradation rate of cellulose nanofibers occurred between 335 °C and 341 °C, with cellulose nanofibers from the basal area being the most stable. The adsorption of the methylene blue dye on cellulose nanofibers was evaluated; an efficiency > 60 % was found.